2023
DOI: 10.21037/jgo-23-33
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel combined with platinum (PTX) versus fluorouracil combined with cisplatin (PF) in the treatment of unresectable esophageal cancer: a systematic review and meta-analysis of the efficacy and toxicity of two different regimens

Abstract: Background: Chemotherapy plays an important role in definitive chemoradiotherapy strategies. However, the most optimal concurrent chemotherapy scheme is still controversial. This study aimed to systematically evaluate the efficacy and toxicity of paclitaxel/docetaxel combined with platinum (PTX) and fluorouracil combined with cisplatin (PF) in the concurrent chemoradiotherapy (CCRT) of unresectable esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The animal model formed by the transplantation of human EC cells into nude mice is more similar to the characteristics of the transplanted tumor and the primary tumor (Cheng et al, 2023). Cisplatin is the first choice in the clinical treatment of EC (Xu et al, 2023), and the therapeutic effect is good, so we use cisplatin as a positive control drug. The results showed that the effect of EP was almost equivalent to that of cisplatin, but the group fed cisplatin is inactive.…”
Section: Discussionmentioning
confidence: 99%
“…The animal model formed by the transplantation of human EC cells into nude mice is more similar to the characteristics of the transplanted tumor and the primary tumor (Cheng et al, 2023). Cisplatin is the first choice in the clinical treatment of EC (Xu et al, 2023), and the therapeutic effect is good, so we use cisplatin as a positive control drug. The results showed that the effect of EP was almost equivalent to that of cisplatin, but the group fed cisplatin is inactive.…”
Section: Discussionmentioning
confidence: 99%
“…Yet only a few rodent models exist for the study of PIPN including ours [28][29][30]. In recent studies, we have shown that paclitaxel administration drives altered behaviors including affective states and nociceptive responses such as mechanical allodynia and thermal hyperalgesia within mice [17,[31][32][33][34][35]. To understand the mechanism that may underlie these sensory responses, we assessed proteomic changes from the DRG in response to a paclitaxel treatment.…”
Section: Drg Proteomics Characterization In a Mouse Model Of Paclitax...mentioning
confidence: 99%
“…In Asia, ESCC is a more common pathological type. Some studies have compared the efficacy of paclitaxel-based regimen and fluorouracil-based regimen in ESCC [ 7 10 ], but there is no consistent conclusion. In the era of immunotherapy, clinical studies have proved that chemotherapy combined with immune checkpoint inhibitors (PD-1 inhibitors) can confer greater benefit to patients with esophageal cancer than chemotherapy alone, especially in ESCC.…”
Section: Introductionmentioning
confidence: 99%